Herding in Aid Allocation - Emmanuel Frot; Javier Santiso (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2009)
Although there exists a vast literature on aid efficiency (the effect of aid on GDP), and that aid allocation determinants have been estimated, little is known about the minute details of aid allocation. This article investigates empirically a claim repeatedly made in the past that aid donors herd. Building upon a methodology applied to financial markets, this article finds that aid donors herd similarly to portfolio funds on financial markets. It also estimates the causes of herding and finds that political transitions towards more autocratic regimes repel donors, but that transitions towards democracy have no effect. Finally, identified causes of herding explain little of its overall level, suggesting strategic motives play an important role.
Keywords: F34; F35; 330; aid; herding; volatility; fragmentation